Rancang Bangun Sistem Informasi Pelaporan Keuangan Menggunakan PSAK 45 pada Panti Asuhan Muhammadiyah Pamekasan - Ramadhan, Gilang Arizky; Binawati, Lilis; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
As one of the foundation which has highly responsibility in orphaned prosperity and eligibility, the orphanage always get public attention. One of the transparancy embodiment could be assess from  financial reporting. The financial reporting should be published for contributor and public. Currently, in Panti Asuhan Muhammadiyah Pamekasan, the financial reporting only based on the revenue of donation and the fund expenditure. Those financial reporting could not represent the orphanage financial condition as globally. That condition made both the contributor and managerial orphanage confused about the condition of orphanage. Besides that, the managerial reporting also was not made by orphanage managerial. Therefore, the orphanage managerial could not make a decision for the future. Based on those conditions, the orphanage should have an information system which could make the complete public financial reporting and managerial reporting. For the public financial reporting, the information system should reference on PSAK 45 (Statement  of Financial Reporting Standard No. 45). The information system could make four standards reporting from PSAK 45 and managerial reporting. By those reports, both contributor and orphanage managerial could know the real financial condition of Panti Asuhan Muhammadiyah Pamekasan.